The impact of high-quality dietary patterns on the prevention of osteoporosis: a meta-analysis of observational studies - Sui, Jing; Yin, Hanlin; Zhang, Linjie; Li, Jiayi (Frontiers in Nutrition, 2025)
Current prevention and treatment strategies for osteoporosis face limitations such as uncertain long-term efficacy, potential safety concerns, and poor adherence. Given these challenges, dietary interventions have emerged as a possible alternative. This study conducts a meta-analysis to systematically evaluate the association between high-quality dietary patterns and osteoporosis risk. We conducted a systematic search of PubMed and Web of Science databases through March 2025. We included observational studies that examined the association between high-quality dietary patterns (HEI, DASH, AHEI, hPDI, MeDS) and osteoporosis. The study selection followed predefined inclusion and exclusion criteria, and the Newcastle-Ottawa Scale was used for quality assessment. A total of 9 articles (including 22 studies) with 243,846 participants were ultimately included. Random-effects model analysis showed that high-quality dietary patterns overall had significant protective effects against osteoporosis (pooled OR = 0.82, 95% CI: 0.72–0.94). Subgroup analyses indicated: DASH (OR = 0.71, 95% CI: 0.57–0.90) and HEI (OR = 0.46, 95% CI: 0.33–0.66) showed significant protective effects. North America (OR = 0.85,95% CI: 0.74–0.97) and Asia (OR = 0.63,95% CI: 0.55–0.72) demonstrated protective effects. A potential protective effect (OR = 0.80,95% CI: 0.70–0.92) was shown in cross-sectional studies. The protective effect was more significant in women (OR = 0.63,95% CI: 0.53–0.74). High-quality dietary patterns, particularly DASH and HEI, may significantly reduce osteoporosis risk. Despite high heterogeneity observed in our study, results from subgroup analyses and meta-regression also supported the integration of dietary pattern into osteoporosis prevention. More cohort studies are warranted to remedy the existing limitation of inadequate longitudinal data, and additional cohort investigations are further essential for validating the observed associations between high-quality dietary patterns and osteoporosis.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251009978.